Coke from SARA fractions in VGO. Impact on Y zeolite acidity and physical properties - Fals Guerra, Jayson (2018)
The impact of the composition of the various hydrocarbon fractions in a conventional VGO (saturated SF, aromatic AF and resin RF) and the whole VGO on the coke formed in their catalytic cracking was evaluated over two Y zeolites with different degree of mesoporosity. The parent zeolite was in its protonic form, Si/Al relationship of 30 and the modified sample was desilicated by alkaline treatment. The fractions were separated from the VGO by means of ASTM D2007-11 method. The catalytic conversion experiments were performed in a batch, fluidized bed laboratory Riser Simulator reactor at 500 °C in the 0.7–3.0 s reaction time range, with a zeolite mass of 0.2 g and a zeolite/reactant mass of 1. Independent of zeolite, fraction SF was the easiest to crack. In the case of the AF fraction, the modified zeolite, with the highest intracrystalline mesoporosity, was more active than the parent zeolite. Gasoline was always the main product, with selectivities from 60 to 70%. All the feedstocks produced more coke on the modified zeolite; however, in spite of the higher coke yields, this zeolite suffered a lower loss of total acidity. As expected, a negative change in both acidity and textural properties (specific surface area and pore volume) were observed as a consequence of the formation of coke. The reactivity of VGO over both zeolites differed from that of fraction SF, even though it was the major fraction (68%). This behavior could be the consequence of interactions between the various fractions composing VGO.